Persepsi Masyarakat Mengenai Keterbukaan Informasi Aparatur Kelurahan dalam Pelaksanaan Program Keluarga Harapan (PKH) di Kelurahan Tarok Dipo Kota Bukittinggi - Aziza Nabela; Nini Sumarni (Lembaga Yasin AlSys, 2026)
The Program Keluarga Harapan (PKH) is a conditional social assistance program that serves as one of the government’s strategies for reducing poverty and improving the welfare of poor families. However, the effectiveness of PKH implementation is not only determined by targeting accuracy, but also by the transparency of urban village officials in conveying the mechanisms, criteria, and data changes concerning aid recipients. This study aimed to analyze the perceptions of the community of Tarok Dipo Urban Village, Bukittinggi City, regarding the transparency of urban village officials in providing information about PKH and to examine its relationship with the principles of maqāṣid syarī‘ah. This study used a qualitative approach with a descriptive design. The research informants consisted of urban village officials, social facilitators, and PKH recipient and non-recipient community members selected purposively. Data were collected through interviews, observation, and documentation, and were then analyzed through the stages of data reduction, data presentation, and conclusion drawing. The results showed that PKH information transparency had been implemented procedurally, but had not been understood evenly by the community. Differences in community perceptions were influenced by limited understanding of changes in the data collection system from DTKS to DTSEN, as well as the suboptimal delivery of information by urban village officials. These findings confirm the importance of clear, consistent, and easily accessible public communication in PKH implementation. The conclusion of this study shows that the transparency of urban village officials’ information needs to be strengthened to improve understanding, trust, and fairness in the distribution of social assistance, while also supporting the principle of public benefit from the perspective of maqāṣid syarī‘ah. Keywords: Program Keluarga Harapan; Community Perception; Information Transparency; Urban Village Officials; Maqāṣid Syarī‘ah